Copper alloy material, and resistor material for resistors and resistors using the same

CN117157419BActive Publication Date: 2026-10-27FURUKAWA ELECTRIC CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280026907.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-06-28
Filing Date
2022-06-24
Publication Date
2026-10-27
Estimated Expiration
2042-06-24

AI Technical Summary

Technical Problem

在这样的电阻器中,在电路中暂时流过大电流的情况下、始终持续流过某种程度的大电流的情况下,在截面积小的电阻材料中产生的焦耳热变高而发热,其结果,存在电阻材料容易因热而断裂(熔断)的不良情况

Benefits of technology

[0029]根据本发明,可提供例如作为电阻材料具有充分高的体积电阻率、并且对铜热电动势的绝对值小,且从常温(例如20℃)到高温(例如150℃)的宽温度范围内的电阻温度系数为负数且绝对值小的铜合金材料以及使用其的电阻器用电阻材料和电阻器。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117157419B_ABST
    Figure CN117157419B_ABST
Patent Text Reader

Abstract

Provided is, for example, a copper alloy material having a sufficiently high volume resistivity as a resistance material and a small absolute value of copper thermoelectric power, and a negative resistance temperature coefficient with a small absolute value in a wide temperature range from normal temperature (for example, 20°C) to high temperature (for example, 150°C), and a resistor resistance material and a resistor using the same. The copper alloy material has an alloy composition containing Mn: 20.0 mass% or more and 35.0 mass% or less, Ni: 5.0 mass% or more and 17.0 mass% or less, and Co: 0.10 mass% or more and 2.00 mass% or less, with the balance being Cu and inevitable impurities. The resistor resistance material is composed of the copper alloy material. In addition, the resistor has the resistor resistance material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to copper alloy materials and resistor materials and resistors using the same. Background Technology

[0002] For resistors made of metallic materials, to ensure stable resistance even with changes in ambient temperature, a small absolute value of the temperature coefficient of resistance (TCR), a key indicator, is required. The temperature coefficient of resistance is a coefficient expressing the change in resistance due to temperature change in parts per million (ppm) per 1°C, denoted by TCR (×10⁻⁶). -6 / ℃)={(R-R0) / R0}×{1 / (T-T0)}×10 6 This is expressed by the formula. Here, T represents the test temperature (°C), T0 represents the reference temperature (°C), R represents the resistance value at the test temperature T (Ω), and R0 represents the resistance value at the reference temperature T0 (Ω). In particular, Cu-Mn-Ni alloys and Cu-Mn-Sn alloys are widely used as alloy materials for constituting resistors because of their very small resistance coefficient (TCR).

[0003] However, for example, in resistors designed to have a specified resistance value by forming a circuit (pattern) using resistive materials, when using Cu-Mn-Ni alloys or Cu-Mn-Sn alloys as resistive materials, it is necessary to reduce the volume resistivity to less than 50 × 10⁻⁶. -8 (Ω·m) This reduces the cross-sectional area of ​​the resistive material and increases the resistance value of the resistor. In such a resistor, when a large current temporarily flows through the circuit, or when a certain level of large current continuously flows through it, the Joule heat generated in the resistive material with a small cross-sectional area increases, resulting in the resistive material being prone to breakage (melting) due to heat.

[0004] Therefore, in order to prevent the cross-sectional area of ​​the resistive material from decreasing, a resistive material with a higher volume resistivity is required.

[0005] For example, in Patent Document 1, in a copper alloy containing Mn in the range of 23% to 28% by mass and Ni in the range of 9% to 13% by mass, by configuring the mass fractions of Mn and Ni such that the thermoelectric potential to copper is less than ±1 μV / ℃ at 20℃, a 50 × 10⁻⁶ N·m³ / h alloy can be obtained. -8 High resistivity (volume resistivity ρ) of [Ω·m] or higher can be obtained, and copper alloys with low copper thermoelectric potential (EMF), low temperature coefficient of resistance and high relative time stability of resistance (time invariance) can be obtained.

[0006] Furthermore, in Patent Document 2, in a copper alloy containing Mn in the range of 21.0% to 30.2% by mass and Ni in the range of 8.2% to 11.0% by mass, the TCR value x [ppm / ℃] in the temperature range of 20°C to 60°C is set to -10 ≤ x ≤ -2 or 2 ≤ x ≤ 10, and the volume resistivity ρ is set to 80 × 10⁻⁶. -8 [Ω·m] above 115×10 -8 [Ω·m] or less, it is possible to suppress the decrease in cross-sectional area of ​​circuits using resistors such as chip resistors that use resistive materials, and it is possible to suppress the increase in Joule heat of resistive materials.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Publication No. 2016-528376

[0010] Patent Document 2: Japanese Patent Application Publication No. 2017-053015 Summary of the Invention

[0011] The problem that the invention aims to solve

[0012] In recent years, in the electrical systems of electric vehicles, resistors such as shunt resistors and chip resistors have been required not only to resistors with high volume resistivity ρ, but also to high-precision resistors that can withstand higher temperature operating environments. As for the copper alloys used in such resistors, high-precision copper alloys that can withstand higher temperature operating environments are also required.

[0013] In response, Patent Document 1 describes a copper alloy in which the thermoelectric potential (EMF) of copper at 20°C is less than ±1 μV / °C. Furthermore, in the copper alloy described in Patent Document 1, as shown in Figure 3, it is known that in the temperature range of 20°C to 150°C, including higher temperature regions, the temperature dependence of the resistance becomes a large negative number. Therefore, the resistance value is prone to error in high-temperature regions, but it is difficult to reduce its absolute value.

[0014] Furthermore, in the copper alloy described in Patent Document 2, the thermoelectric potential (EMF) generated between 20°C and 100°C is set to ±2μV / °C or less, and the temperature dependence of the resistance is set to ±50×10⁻⁶ within the temperature range of 20°C to 60°C. -6 [℃ -1 The range below, but requires further reduction of the absolute value of EMF, and control of the temperature coefficient of resistance (TCR) over a wide temperature range from room temperature (e.g., 20°C) to high temperature (e.g., 150°C) to a small negative absolute value.

[0015] Thus, for the copper alloys described in Patent Documents 1 and 2, there is room for improvement in terms of increasing the volume resistivity ρ and considering the operating environment over a wide temperature range from room temperature to high temperature, as well as the temperature coefficient of resistance (TCR) and the thermoelectric potential (EMF) of copper, by reducing the absolute value of the thermoelectric potential (EMF) of copper and setting the temperature coefficient of resistance (TCR) to a negative number with a small absolute value.

[0016] Therefore, the object of the present invention is to provide, for example, a copper alloy material having a sufficiently high volume resistivity as a resistive material, a small absolute value of the thermoelectric potential of copper, and a negative temperature coefficient of resistance with a small absolute value over a wide temperature range from room temperature (e.g., 20°C) to high temperature (e.g., 150°C), as well as a resistive material and a resistor using the copper alloy material.

[0017] Methods for solving problems

[0018] The inventors of this application achieved the following insight, thereby completing the present invention. That is, by having an alloy composition containing Mn: 20.0% to 35.0% by mass, Ni: 5.0% to 17.0% by mass, and Co: 0.10% to 2.00% by mass, with the balance being Cu and unavoidable impurities, a copper alloy material can be obtained, for example, as a resistive material, having a sufficiently high volume resistivity ρ, a small absolute value of the copper thermoelectric potential (EMF), and a negative temperature coefficient of resistance with a small absolute value over a wide temperature range from room temperature (e.g., 20°C) to high temperature (e.g., 150°C).

[0019] To achieve the above objectives, the main components of the present invention are as follows.

[0020] (1) A copper alloy material having the following alloy composition, wherein the alloy composition contains: Mn: 20.0% by mass or more and 35.0% by mass, Ni: 5.0% by mass or more and 17.0% by mass, and Co: 0.10% by mass or more and 2.00% by mass, with the balance being Cu and unavoidable impurities.

[0021] (2) The copper alloy material as described in (1) above, wherein when the content of Mn is set as x [mass%], the content of Ni is set as y [mass%], and the content of Co is set as z [mass%], x, y and z satisfy the relationship of equation (I) as shown below.

[0022] 0.8x-10.5≤y+5z≤0.8x-6.5(I).

[0023] (3) The copper alloy material as described in (1) or (2) above, wherein when the content of Mn is set as x [mass%] and the content of Ni is set as y [mass%], the ratio of y to x is less than 0.40.

[0024] (4) The copper alloy material as described in (1), (2) or (3) above, wherein the alloy composition further comprises at least one element selected from the group consisting of Sn: 0.01% to 3.00% by mass, Zn: 0.01% to 5.00% by mass, Cr: 0.01% to 0.50% by mass, Ag: 0.01% to 0.50% by mass, Al: 0.01% to 1.00% by mass, Mg: 0.01% to 0.50% by mass, Si: 0.01% to 0.50% by mass, and P: 0.01% to 0.50% by mass.

[0025] (5) The copper alloy material as described in any one of (1) to (4) above, wherein the copper alloy material is a plate, rod, strip or wire, and the average crystal grain size is less than 60 μm.

[0026] (6) A resistor material for a resistor, comprising any one of the copper alloy materials described in (1) to (5) above.

[0027] (7) A resistor, which is a shunt resistor or a chip resistor having the resistor material described in (6) above.

[0028] Invention Effects

[0029] According to the present invention, copper alloy materials, for example, having a sufficiently high volume resistivity as a resistive material, a small absolute value of the thermoelectric potential of copper, and a negative temperature coefficient of resistance with a small absolute value over a wide temperature range from room temperature (e.g., 20°C) to high temperature (e.g., 150°C), as well as resistive materials and resistors using the same, can be provided. Attached Figure Description

[0030] [ Figure 1 For copper alloy materials containing Mn, Ni, and Co, a graph is shown showing the relationship between x and (y+5z) when the Mn content is set as x [mass%], the Ni content as y [mass%], and the Co content as z [mass%]. The graph is plotted with x as the horizontal axis and (y+5z) as the vertical axis.

[0031] [ Figure 2 This is a schematic diagram illustrating the method for determining the thermoelectric potential (EMF) of copper for the test materials of the present invention and comparative examples. Detailed Implementation

[0032] The preferred embodiments of the copper alloy material of the present invention will be described in detail below. Furthermore, in the composition of the alloy of the present invention, "mass %" is sometimes simply expressed as "%".

[0033] The copper alloy material of the present invention has an alloy composition containing Mn: 20.0% to 35.0% by mass, Ni: 5.0% to 17.0% by mass, and Co: 0.10% to 2.00% by mass, with the balance being Cu and unavoidable impurities.

[0034] Thus, in the copper alloy material of the present invention, by containing Mn in the range of 20.0% to 35.0% by mass, Ni in the range of 5.0% to 17.0% by mass, and Co in the range of 0.10% to 2.00% by mass, the absolute value of the thermoelectric potential (EMF) generated between 0°C and 80°C (hereinafter, sometimes simply referred to as "thermoelectric potential") is reduced compared to the case without Co. Therefore, even at high temperature environments, the high precision of the resistor can be promoted. In addition, by containing Mn in the range of 20.0% to 35.0% by mass and Ni in the range of 5.0% to 17.0% by mass, the volume resistivity ρ can be increased, and the absolute value of the thermoelectric potential can be reduced. As a result, by using the copper alloy material of the present invention, a copper alloy material having a sufficiently high volume resistivity ρ as a resistive material and a small absolute value of the thermoelectric potential (EMF) can be provided, as well as a resistor material and a resistor using the same.

[0035] Furthermore, in the copper alloy material of the present invention, it is also possible to reduce the absolute value of the temperature coefficient of resistance (TCR) (hereinafter sometimes simply referred to as "temperature coefficient of resistance") over a wide temperature range from room temperature (e.g., 20°C) to high temperature (e.g., 150°C). In this regard, in the copper alloys described in Patent Documents 1 and 2, the temperature dependence of resistance is described as ±50 × 10⁻⁶ in the temperature range of 20°C to 60°C. -6 [℃ -1 The following range. Regarding this, as described in Figure 3 of Patent Document 1, it is known that in the temperature range from 20°C to 150°C, including higher temperature regions, the temperature dependence of resistance is a large negative number, and therefore the resistance value is prone to error in the high-temperature region. In this regard, in the copper alloy material of the present invention, the absolute value of the temperature coefficient of resistance (TCR) can be reduced over a wide temperature range from room temperature (e.g., 20°C) to high temperature (e.g., 150°C).

[0036] Furthermore, in the copper alloy material of the present invention, it is possible to make the temperature coefficient of resistance (TCR) (hereinafter sometimes simply referred to as "temperature coefficient of resistance") negative from room temperature (e.g., 20°C) to high temperature (e.g., 150°C). More specifically, by containing Mn in the range of 20.0% to 35.0% by mass, Ni in the range of 5.0% to 15.0% by mass, and Co in the range of 0.10% to 2.00% by mass, it is possible to make the value of the temperature coefficient of resistance (TCR) negative in the temperature range of 20°C to 150°C, including the higher temperature region. As a result, when the copper alloy material is used as a resistive material such as a resistor, the adverse effects caused by the high temperature coefficient of resistance of the metal that is the conductor bonded to the copper alloy material can be mitigated. For example, when the metal that is the conductor is copper, since the temperature coefficient of resistance of copper is about 4000 ppm / °C, which is relatively large, the resistance value will vary due to the temperature change of the conductor. In this regard, by using copper alloy materials with a negative temperature coefficient of resistance (TCR), the adverse effects of temperature changes on the resistance value of the conductor can be mitigated.

[0037] Therefore, in the copper alloy material of the present invention, it is possible to provide a copper alloy material having a high volume resistivity ρ, a small absolute value of copper thermoelectric potential (EMF), and a negative temperature coefficient of resistance (TCR) with a small absolute value, as well as a resistor material and a resistor using the same.

[0038] [1] Composition of copper alloy materials

[0039] <Required Ingredients>

[0040] The copper alloy material of the present invention contains, as essential components, Mn: 20.0% to 35.0% by mass, Ni: 5.0% to 17.0% by mass, and Co: 0.10% to 2.00% by mass.

[0041] (Mn: ≥20.0% by mass and ≤35.0% by mass)

[0042] Manganese (Mn) is an element that increases the volume resistivity ρ and, by adjusting the temperature coefficient of resistance (TCR) in a positive direction, readily produces a small negative absolute value for the TCR. To achieve this effect and obtain a homogeneous copper alloy material, Mn preferably contains 20.0% by mass or more, more preferably 22.0% by mass or more, and even more preferably 24.0% by mass or more. Here, by increasing the Mn content to 22.0% by mass or more, or 24.0% by mass or more, the volume resistivity ρ of the copper alloy material can be further increased. On the other hand, if the Mn content exceeds 35.0% by mass, it becomes difficult to reduce the absolute values ​​of the copper thermoelectric potential (EMF) and the temperature coefficient of resistance (TCR). In particular, if the Mn content exceeds 35.0% by mass, the copper thermoelectric potential (EMF) tends to increase in a negative direction. Therefore, the Mn content is preferably in the range of 20.0% by mass or more and 35.0% by mass or less.

[0043] (Ni: 5.0% by mass to 17.0% by mass)

[0044] Ni (Ni) is an element that reduces the absolute value of the thermoelectric potential (EMF) of copper. To achieve this effect, Ni preferably contains 5.0% by mass or more. On the other hand, a high Ni content tends to result in a large negative absolute value for the temperature coefficient of resistance (TCR). Therefore, the Ni content is preferably in the range of 5.0% by mass or more to 17.0% by mass or less. In particular, for the Ni content in the copper alloy material of the present invention, when the Mn content is set as x [mass%] and the Ni content as y [mass%], the ratio of y to x is preferably less than 0.40. By reducing the ratio of y to x, the absolute value of the temperature coefficient of resistance (TCR) can be further reduced. Therefore, the ratio of y to x is preferably less than 0.40, more preferably 0.38 or less, and even more preferably 0.36 or less. It should be noted that, from the viewpoint of reducing the absolute value of the temperature coefficient of resistance (TCR), the Ni content in the copper alloy material can be in the range of 5.0% by mass or more to 10.0% by mass or less.

[0045] (Co: 0.10% by mass to 2.00% by mass)

[0046] Co (Cobalt) is an element that reduces the absolute value of the thermoelectric potential (EMF) of copper by adjusting it in the positive direction. To achieve this effect, Co preferably contains 0.10% by mass or more, more preferably 0.20% by mass or more, and even more preferably 0.30% by mass or more. In particular, in the copper alloy material of the present invention, by combining Co and Ni, compared to the case containing only Ni, either the absolute value of the thermoelectric potential (EMF) or the absolute value of the temperature coefficient of resistance (TCR) can be reduced. Furthermore, by keeping the Co content in the range of 0.10% by mass to 2.00% by mass, compared to the case containing Fe (iron), it is easier to obtain a single phase, thus making it easier to manufacture copper alloy materials with small deviations in electrical properties. On the other hand, if the Co content is high, the temperature coefficient of resistance (TCR) tends to become a large negative value. Additionally, the thermoelectric potential (EMF) tends to become a large positive value. Therefore, the Co content is preferably in the range of 0.10% by mass to 2.00% by mass.

[0047] The copper alloy material of the present invention contains Mn, Ni and Co, and when the content of Mn is set as x [mass%], the content of Ni is set as y [mass%] and the content of Co is set as z [mass%], x, y and z preferably satisfy the relationship shown in equation (I) below.

[0048] 0.8x-10.5≤y+5z≤0.8x-6.5(I)

[0049] Specifically, by satisfying the relationship 0.8x-10.5≤y+5z, the copper thermoelectric potential (EMF) is less likely to take a large value in the negative direction. On the other hand, by satisfying the relationship y+5z≤0.8x-6.5, the copper thermoelectric potential (EMF) is less likely to take a large value in the positive direction.

[0050] Figure 1 This graph, specifically for copper alloys containing Mn, Ni, and Co, shows the relationship between x and (y+5z) when the Mn content is set as x [mass %], the Ni content as y [mass %], and the Co content as z [mass %]. The graph is plotted with x on the horizontal axis and (y+5z) on the vertical axis. Figure 1 In the diagram, copper alloy materials with an absolute value of 0.5 μV / ℃ or less for the thermoelectric potential (EMF) of copper are marked with "○" because of their small absolute value of EMF and good resistance. Conversely, copper alloy materials with an absolute value of EMF exceeding 0.5 μV / ℃ are marked with "×" because of their large absolute value of EMF and unacceptable resistance.

[0051] Here, for copper alloy materials containing Mn, Ni, and Co, and satisfying the relationship in equation (I) above, and more specifically for the copper alloy materials of Examples 1 to 18 and Comparative Example 4 of the present invention described later, the absolute value of the copper thermoelectric potential (EMF) is 0.5 μV / ℃ or less. Figure 1 In the figures, all are marked with "○". On the other hand, for copper alloys containing Mn, Ni, and Co that do not satisfy the above relationship (I), such as the copper alloys of Comparative Examples 2, 3, 5-7 described later, the absolute value of the copper thermoelectric potential (EMF) exceeds 0.5 μV / ℃. Figure 1 In the diagram, all are marked with "×".

[0052] Thus, by satisfying the relationship in equation (I) above, copper alloy materials with small absolute values ​​of copper thermoelectric potential (EMF) (e.g., less than 0.5 μV / ℃) can be easily obtained.

[0053] In addition, Figure 1 Among the copper alloy materials that do not satisfy the relationship in equation (I) above, in addition to Comparative Examples 2, 3, 5-7, various copper alloy materials containing Mn, Ni, and Co have been described. However, the absolute values ​​of their copper thermoelectric potentials (EMF) all exceed 0.5 μV / ℃. Figure 1 The figure is marked with "×".

[0054] <Optional Added Ingredients>

[0055] The copper alloy material of the present invention may, as an optional additive, further contain at least one component selected from the group consisting of Sn: 0.01% to 3.00% by mass, Zn: 0.01% to 5.00% by mass, Cr: 0.01% to 0.50% by mass, Ag: 0.01% to 0.50% by mass, Al: 0.01% to 1.00% by mass, Mg: 0.01% to 0.50% by mass, Si: 0.01% to 0.50% by mass, and P: 0.01% to 0.50% by mass.

[0056] (Sn: ≥0.01% by mass ≤3.00% by mass)

[0057] Sn (tin) is a component that can be used to adjust the volume resistivity ρ. To achieve this effect, it is preferable to have a Sn content of 0.01% by mass or more. On the other hand, by keeping the Sn content below 3.00% by mass, the reduction in manufacturability caused by embrittlement of the copper alloy material is less likely to occur.

[0058] (Zn: ≥0.01% by mass ≤5.00% by mass)

[0059] Zinc (Zn) is a component that can be used to adjust the volume resistivity ρ. To achieve this effect, it is preferable to have a Zn content of 0.01% by mass or more. On the other hand, the Zn content may adversely affect the stability of the electrical properties of resistors, such as volume resistivity ρ, temperature coefficient of resistance (TCR), and copper thermoelectric potential (EMF), so it is preferable to set it to 5.00% by mass or less.

[0060] (Cr: ≥0.01% by mass to ≤0.50% by mass)

[0061] Cr (chromium) is a component that can be used to adjust the volume resistivity ρ. To achieve this effect, it is preferable to contain 0.01% by mass or more of Cr. On the other hand, the Cr content may adversely affect the stability of the electrical properties of resistors, such as volume resistivity ρ, temperature coefficient of resistance (TCR), and copper thermoelectric potential (EMF), so it is preferable to contain 0.50% by mass or less.

[0062] (Ag: ≥0.01% by mass and ≤0.50% by mass)

[0063] Silver (Ag) is a component that can be used to adjust the volume resistivity ρ. To achieve this effect, it is preferable to contain 0.01% by mass or more of Ag. On the other hand, the Ag content may adversely affect the stability of the electrical properties of resistors such as volume resistivity ρ, temperature coefficient of resistance (TCR), and copper thermoelectric potential (EMF), so it is preferable to contain 0.50% by mass or less.

[0064] (Al: 0.01% by mass to 1.00% by mass)

[0065] Al (aluminum) is a component that can be used to adjust the volume resistivity ρ. To achieve this effect, it is preferable to have an Al content of 0.01% by mass or more. On the other hand, since it may cause embrittlement of copper alloy materials, it is preferable to have an Al content of 1.00% by mass or less.

[0066] (Mg: ≥0.01% by mass to ≤0.50% by mass)

[0067] Magnesium (Mg) is a component that can be used to adjust the volume resistivity ρ. To achieve this effect, it is preferable to contain 0.01% by mass or more of Mg. On the other hand, since it may cause embrittlement of copper alloy materials, the Mg content is preferably 0.50% by mass or less.

[0068] (Si: 0.01% by mass or more, less than 0.50% by mass)

[0069] Silicon (Si) is a component that can be used to adjust the volume resistivity ρ. To achieve this effect, it is preferable to contain 0.01% by mass or more of Si. On the other hand, since it may cause embrittlement of copper alloy materials, the Si content is preferably 0.50% by mass or less.

[0070] (P: ≥0.01% by mass and ≤0.50% by mass)

[0071] Phosphorus (P) is a component that can be used to adjust the volume resistivity (ρ). To achieve this effect, it is preferable to have a P content of 0.01% by mass or more. On the other hand, since it may cause embrittlement of copper alloy materials, the P content is preferably 0.50% by mass or less.

[0072] (Total amount of optional added ingredients: 0.01% by mass to 5.00% by mass)

[0073] To achieve the effects of the optional additives mentioned above, these optional additives are preferably present in a total of 0.01% by mass or more. On the other hand, if these optional additives are present in large quantities, they are more likely to form compounds with the essential ingredients; therefore, the total amount is preferably 5.00% by mass or less.

[0074] Balance: Cu and unavoidable impurities

[0075] Besides the required and optional ingredients mentioned above, the balance consists of Cu (copper) and unavoidable impurities. It should be noted that "unavoidable impurities" in copper-based products generally refer to substances present in the raw materials or unavoidably introduced during the manufacturing process. These are substances that are not inherently desirable, but because they are present in trace amounts and do not affect the properties of the copper-based products, they are permissible impurities. Examples of unavoidable impurities include non-metallic elements such as sulfur (S), carbon (C), and oxygen (O), and metallic elements such as antimony (Sb). It should be noted that the upper limit for the content of these components is 0.05% by mass for each of the above components, or 0.10% by mass for the total amount of the above components.

[0076] [2] Shape and metal structure of copper alloy materials

[0077] The shape of the copper alloy material of the present invention is not particularly limited, but from the viewpoint of facilitating the hot or cold processing steps described later, it is preferably a plate, bar, strip, or wire. In copper alloy materials formed by rolling, such as plates or strips, the rolling direction can be set as the stretching direction. Furthermore, in copper alloy materials formed by drawing, stretching, or extruding wires or bars, such as flat wires or round wires, any one of the drawing direction, stretching direction, or extrusion direction can be used as the stretching direction.

[0078] Furthermore, the copper alloy material of the present invention is preferably in the form of sheet, bar, strip, or wire, and its average crystal grain size is 60 μm or less. Here, by ensuring that the average crystal grain size of the crystals contained in the copper alloy material is 60 μm or less, coarse grains are less likely to form on the copper alloy material, thus simultaneously reducing the absolute value of the temperature coefficient of resistance (TCR) and the absolute value of the thermoelectric potential (EMF) of copper. In particular, the copper alloy material of the present invention contains Co, which makes it less prone to phase transformation, thus easily obtaining a copper alloy material with an average crystal grain size of 60 μm or less. On the other hand, the lower limit of the average crystal grain size is not particularly limited, and from a manufacturing point of view, it can be 0.1 μm or more. It should be noted that the average crystal grain size is measured on a plane orthogonal to the stretching direction when the crystals are not formed in an equiaxed shape and the grain size is anisotropic due to processing such as rolling or drawing along the stretching direction.

[0079] Here, the determination of the average crystal grain size in this specification can be performed according to the test method for crystal grain size of copper alloys as described in JIS H0501. More specifically, after preparing the test material by embedding it in resin with the cross-section of the copper alloy material exposed, the cross-section orthogonal to the stretching direction is ground, followed by wet etching with an aqueous chromic acid solution. The exposed grains are then observed using a scanning electron microscope (SEM) to determine the crystal grain size (or crystal grain size). In particular, when determining the average crystal grain size on the surface orthogonal to the stretching direction, the test material is prepared by embedding the cross-section of the copper alloy material orthogonal to the stretching direction in resin.

[0080] [3] An example of a manufacturing method for copper alloy materials

[0081] The aforementioned copper alloy materials can be achieved by combining and controlling the alloy composition and manufacturing process, and the manufacturing process is not particularly limited. As an example of a manufacturing process that can obtain the aforementioned copper alloy materials, the following method can be cited.

[0082] As an example of the method for manufacturing the copper alloy material of the present invention, a copper alloy raw material having an alloy composition substantially the same as that of the copper alloy material described above is subjected to at least the following steps in sequence: casting process [step 1], homogenization heat treatment process [step 2], hot working process [step 3], cold working process [step 4], and annealing process [step 5]. In the casting process [step 1], the copper alloy raw material is melted in an inert gas atmosphere or in a vacuum to produce an ingot. In the homogenization heat treatment process [step 2], the heating temperature is set to a range of 750°C to 900°C, and the holding time at the heating temperature is set to a range of 10 minutes to 10 hours. In the annealing process [step 5], the heating temperature is set to a range of 600°C to 800°C, and the holding time at the heating temperature is set to a range of 1 minute to 2 hours.

[0083] (i) Casting process [Process 1]

[0084] In the casting process [Process 1], a high-frequency melting furnace is used to melt and cast a copper alloy raw material having the above-mentioned alloy composition in an inert gas atmosphere or vacuum, thereby producing a casting (ingot) of a specified shape (e.g., 30 mm thick, 50 mm wide, and 300 mm long). It should be noted that, regarding the alloy composition of the copper alloy raw material, although the alloy composition may not be completely consistent with the alloy composition of the manufactured copper alloy material due to the different additives in each manufacturing process, the alloy composition is substantially the same as that of the copper alloy material.

[0085] (ii) Homogenization heat treatment process [Process 2]

[0086] The homogenization heat treatment process [process 2] is a process of performing homogenization heat treatment on the ingot after the casting process [process 1]. Here, regarding the conditions of the heat treatment in the homogenization heat treatment process [process 2], from the viewpoint of suppressing grain coarsening, it is preferable to set the heating temperature to a range of 750°C to 900°C and the holding time at the heating temperature to a range of 10 minutes to 10 hours.

[0087] (iii) Hot working process [Process 3]

[0088] The hot working process [process 3] is a process of producing hot-rolled material by hot rolling, drawing, etc., of the cast ingot that has undergone homogenization heat treatment until it reaches the specified thickness and dimensions. Here, the hot working process [process 3] includes both hot rolling and hot drawing (wire drawing) processes. In terms of the conditions of the hot working process [process 3], the processing temperature is preferably in the range of 750°C to 900°C, and may also be the same as the heating temperature in the homogenization heat treatment process [process 2]. In addition, the processing rate in the hot working process [process 3] is preferably 10% or more.

[0089] Here, "processing rate" is a percentage value expressed by subtracting the processed cross-sectional area from the cross-sectional area before processing such as rolling and drawing, divided by the cross-sectional area before processing, and then multiplied by 100.

[0090] [Processing Rate] = {([Cross-sectional area before processing] - [Cross-sectional area after processing]) / [Cross-sectional area before processing]} × 100 (%)

[0091] After the hot-working process [process 3], the hot-rolled material is preferably cooled. Here, there is no particular limitation on the method of cooling the hot-rolled material. For example, from the viewpoint of making it less likely for grain coarsening to occur, it is preferable to use a method that increases the cooling rate as much as possible. For example, it is preferable to use a method such as water cooling to make the cooling rate 10°C / second or more.

[0092] Here, surface cutting can also be performed on the cooled hot-rolled material to remove surface defects. By performing surface cutting, the oxide film and defects generated on the surface in the hot working process [process 3] can be removed. The conditions for surface cutting are not particularly limited as long as they are the usual conditions. The amount removed from the surface of the hot-rolled material by surface cutting can be appropriately adjusted based on the conditions of the hot working process [process 3], for example, it can be set to about 0.5 to 4 mm from the surface of the hot-rolled material.

[0093] (iv) Cold working process [process 4]

[0094] The cold working process [process 4] is a process in which hot-rolled material that has undergone the hot working process [process 3] is rolled, drawn, or processed in a cold room at an arbitrary processing rate according to the thickness or wire diameter and size of the product. Here, the cold working process [process 4] includes both a cold rolling process and a cold drawing (wire drawing) process. In addition, the rolling, drawing, and other conditions in the cold working process [process 4] can be set according to the size of the hot-rolled material. In particular, in the annealing process [process 5] described later, from the viewpoint of promoting the formation of uniform grains caused by recrystallization, it is preferable to make the total processing rate in the cold working process [process 4] 50% or more.

[0095] (v) Annealing process [Process 5]

[0096] The annealing process [Process 5] is a heat treatment process that causes the cold-rolled material, after the cold working process [Process 4], to recrystallize. In the heat treatment conditions of the annealing process [Process 5], the heating temperature is in the range of 600°C to 800°C, and the holding time at the heating temperature is in the range of 1 minute to 2 hours. On the other hand, when the heating temperature is below 600°C and the holding time is less than 1 minute, it is difficult to recrystallize the copper alloy material. Furthermore, when the heating temperature exceeds 800°C and the holding time exceeds 2 hours, due to grain coarsening, the absolute values ​​of the temperature coefficient of resistance (TCR) and the thermoelectric potential (EMF) of copper tend to increase.

[0097] Here, the cold-rolled material after the annealing process [process 5] can also be repeatedly subjected to the cold working process [process 4] and the annealing process [process 5]. As a result, the copper alloy material becomes a plate, bar, strip, or wire with the desired shape, and coarse grains are not easily formed. Therefore, it is possible to obtain a copper alloy material that exhibits the desired characteristics in terms of volume resistivity, temperature coefficient of resistance, and thermoelectric potential of copper.

[0098] [8] Applications of copper alloy materials

[0099] In addition to plates and rods, the copper alloy material of the present invention can also be in the form of strips such as bar stock, flat wires, and round wires, making it extremely useful as a resistor material for resistors such as shunt resistors and chip resistors. That is, the resistor material for resistors preferably includes the aforementioned copper alloy material. Furthermore, resistors such as shunt resistors or chip resistors preferably have a resistor material for resistors that includes the aforementioned copper alloy material.

[0100] The embodiments of the present invention have been described above, but the present invention is not limited to the above embodiments, and includes all the concepts and methods contained in the claims, and various changes can be made within the scope of the present invention.

[0101] Example

[0102] Next, in order to further clarify the effects of the present invention, examples and comparative examples of the present invention will be described, but the present invention is not limited to these embodiments.

[0103] (Examples 1-13 of the present invention and Comparative Examples 1-8)

[0104] A casting process [Process 1] was performed, in which copper alloy raw materials having the alloy composition shown in Table 1 were melted, cooled from the molten metal, and cast to obtain an ingot. Here, the alloy composition of Comparative Example 1 is the same as that of the copper alloy described in Patent Document 1. In addition, the alloy composition of Comparative Example 8 is the same as that of the copper alloy described in Patent Document 2.

[0105] The casting is subjected to a homogenization heat treatment process [Step 2], which involves heating at 800°C and holding for 5 hours. Then, it undergoes a hot-working process [Step 3], where it is rolled along its length at a processing temperature of 800°C with a total machining rate of 73% (thickness before machining is 30 mm, thickness after machining is 8 mm), to obtain a hot-rolled material. Finally, it is cooled to room temperature by water cooling and surface cutting is performed to remove the oxide film formed on the surface.

[0106] The hot-rolled material after the hot working process [Process 3] undergoes a cold working process [Process 4], rolling it along its length at a total processing rate of 88% (thickness before processing is 8 mm, thickness after processing is 1 mm). The rolled material after the cold working process [Process 4] undergoes an annealing process [Process 5], heat-treated at a temperature ranging from 600°C to 800°C for a holding time of 1 minute to 2 hours.

[0107] Furthermore, the hot-rolled material after the annealing process [Process 5] is subjected to a second cold working process [Process 4], in which it is rolled along the length direction at a total processing rate of 70% (thickness before processing is 1 mm, thickness after processing is 0.3 mm). The cold-rolled material after the second cold working process [Process 4] is subjected to a second annealing process [Process 5], in which it is heated at a temperature ranging from 600°C to 800°C and held for a holding time of 1 minute to 2 hours. In this manner, copper alloy sheets of Examples 1 to 13 and Comparative Examples 1 to 8 of the present invention with adjusted crystal grain size were manufactured.

[0108] It should be noted that in Table 1, the column for components not included in the alloy composition of copper alloy raw materials is marked with a horizontal line "-", which clarifies that the component is not present or, even if it is present, the content is below the detection threshold.

[0109] (Example 14 of this invention)

[0110] A casting process [Step 1] is performed, in which copper alloy raw material with the alloy composition shown in Table 1 is melted, cooled from the molten metal to 300°C, and then cast to obtain an ingot with a diameter of 30 mm. The ingot is then subjected to a homogenization heat treatment process [Step 2], where it is heated to 800°C and held for 5 hours. Next, a hot working process [Step 3] is performed, whereby the ingot is stretched along its length in a single rolling operation at a processing temperature of 800°C to achieve a total processing rate of 11%, resulting in a bar stock as hot-rolled material (the diameter of the ingot before processing is 30 mm, and the diameter of the bar stock after processing is 10 mm). Finally, the bar stock is cooled to room temperature by water cooling and then surface-cut to remove the oxide film formed on its surface.

[0111] The bar stock after the hot working process [Step 3] is subjected to a cold working process [Step 4], namely, drawing with a circular die to achieve a total processing rate of 95% (the diameter of the bar stock before processing is 9 mm, and the diameter of the round wire after processing is 1.95 mm). The cold-rolled material after the cold working process [Step 4] is subjected to an annealing process [Step 5], which involves heating at a temperature between 600°C and 800°C and holding for a time between 1 minute and 2 hours. As a result, the copper alloy wire of Example 14 of the present invention with adjusted crystal grain size is produced.

[0112] (Examples 15-18 of this invention)

[0113] For the bar stock obtained in the same hot working process [step 3] as in Example 14 of the present invention, a cold working process [step 4] is performed, that is, drawing is performed using a flat die with a curvature radius of 0.1 mm at the four corners, thereby drawing wire with a total processing rate of 95% (the diameter of the bar stock before processing is 9 mm, and the thickness of the flat wire after processing is 1 mm and the width is 3 mm). The cold-rolled material after the cold working process [step 4] is then subjected to an annealing process [step 5], which involves heating the material at a temperature between 600°C and 800°C for a holding time of 1 minute to 2 hours.

[0114] Furthermore, the hot-rolled material after the annealing process [Process 5] is subjected to a second cold working process [Process 4], in which it is rolled along its length at a total processing rate of 70% (thickness before processing is 1 mm, and thickness after processing is 0.3 mm). The cold-rolled material after the second cold working process [Process 4] is subjected to a second annealing process [Process 5], in which it is heated at a temperature between 600°C and 800°C and held for a time between 1 minute and 2 hours. In this way, copper alloy wires of Examples 15 to 18 of the present invention with adjusted crystal grain size are produced.

[0115] [Various measurement and evaluation methods]

[0116] Using the copper alloy materials (copper alloy plates, copper alloy wires) described in the above-described examples and comparative examples of the present invention, the following characteristic evaluations were performed. The evaluation conditions for each characteristic are as follows.

[0117] [1] Determination of average crystal grain size

[0118] For the prepared copper alloy material, a test material was prepared by embedding it in resin with a cross-section exposed orthogonally to the tensile direction of the copper alloy material. The cross-section orthogonal to the tensile direction was then ground. Next, the ground test material was wet-etched using an aqueous chromic acid solution. The exposed grains were then observed using a scanning electron microscope (SEM) (Shimadzu Corporation, model: SSX-550). Three fields of view were examined at magnifications from 50x to 2000x based on the average grain size. The grain size was determined using the cutting method within the test method for grain size of stretched copper products described in JIS H 0501. The average grain size was calculated as the average of the grain sizes in the three fields of view. The results are shown in Table 2.

[0119] [2] Determination of volume resistivity

[0120] For Examples 1-13 and Comparative Examples 1-8 of the present invention, which yielded sheet materials, the sheet materials with a thickness of 0.3 mm were cut into pieces 10 mm wide and 300 mm long to prepare test materials. Additionally, for Examples 14-18 of the present invention, which yielded round or flat wires, the round or flat wires were cut into pieces 300 mm long to prepare test materials.

[0121] In the determination of volume resistivity ρ, the distance between voltage terminals is set to 200 mm and the measurement current is set to 100 mA. The voltage is measured at room temperature of 23 °C using the four-terminal method based on the method specified in JIS C2525. The volume resistivity ρ [μΩ·cm] is then calculated from the obtained value.

[0122] Regarding the measured volume resistivity ρ, cases with ρ above 80 μΩ·cm are evaluated as having sufficiently high volume resistivity ρ and are excellent as resistive materials, and are rated "◎". Conversely, cases with volume resistivity ρ above 70 μΩ·cm and less than 80 μΩ·cm are evaluated as having high volume resistivity ρ and are good as resistive materials, and are rated "○". On the other hand, cases with volume resistivity ρ less than 70 μΩ·cm are evaluated as having low volume resistivity ρ and are poor as resistive materials, and are rated "×". In this embodiment, "◎" and "○" are evaluated as acceptable levels. The results are shown in Table 2.

[0123] [3] Method for determining the electromotive force (EMF) of copper thermoelectric potential

[0124] For Examples 1-13 and Comparative Examples 1-8 of the present invention, which yielded sheet materials, the sheet materials with a thickness of 0.3 mm were cut into pieces 10 mm wide and 1000 mm long to prepare test materials. Furthermore, for Examples 14-18 of the present invention, which yielded round or flat wires, the round or flat wires were cut into pieces 1000 mm long to prepare test materials.

[0125] The thermoelectric potential (EMF) of the test material to copper was determined according to JIS C2527. More specifically, such as Figure 2 As shown, in the determination of the copper thermoelectric potential (EMF) of test material 1, a fully annealed pure copper wire with a diameter of 1 mm was used as the standard copper wire 2. The temperature measuring contact P1, which connects one end of test material 1 and standard copper wire 2, was immersed in warm water kept at 80°C in a constant temperature bath 41. The reference contact P1, which connects the other end of test material 1 and standard copper wire 2 to copper wires 31 and 32 respectively, was used as the reference contact. 21 P 22 The copper is immersed in ice water at 0°C, kept cool by freezing device 42, and the electromotive force is measured by voltage measuring device 43. The obtained electromotive force is divided by 80°C, which is the temperature difference, to obtain the thermoelectric potential EMF (μV / °C) for copper.

[0126] Regarding the measured thermoelectric potential (EMF) of copper, cases with an absolute value below 0.5 μV / ℃ were considered to have a small absolute value of EMF and were evaluated as good resistive materials, and were marked with "◎". On the other hand, cases with an absolute value of EMF greater than 0.5 μV / ℃ were considered to have a large absolute value of EMF and were evaluated as poor resistive materials, and were marked with "×". The results are shown in Table 2.

[0127] [4] Method for determining the temperature coefficient of resistance (TCR)

[0128] For Examples 1-13 and Comparative Examples 1-8 of the present invention, which yielded sheet materials, the sheet materials with a thickness of 0.3 mm were cut into pieces 10 mm wide and 300 mm long to prepare test materials. Additionally, for Examples 14-18 of the present invention, which yielded round or flat wires, the round or flat wires were cut into pieces 300 mm long to prepare test materials.

[0129] In the determination of the temperature coefficient of resistance (TCR), the distance between voltage terminals is set to 200 mm and the measuring current is set to 100 mA. The voltage at which the test material is heated to 150 °C is measured using the four-terminal method based on the method specified in JIS C2526. The resistance value R at 150 °C is then calculated from the obtained value. 150℃ [mΩ]. Next, the voltage was measured when the test material was cooled to 20°C, and the resistance value R at 20°C was calculated from the obtained value. 20℃ [mΩ]. Then, based on the obtained resistance value, R... 150℃ and R 20℃ The value is determined by TCR = {(R 150℃ [mΩ]-R 20℃ [mΩ]) / R 20℃ [mΩ]}×{1 / (150[℃]-20[℃])}×106 The formula is used to calculate the temperature coefficient of resistance (ppm / ℃).

[0130] Regarding the measured temperature coefficient of resistance (TCR), cases with a TCR between -50 ppm / ℃ and 0 ppm / ℃ were considered excellent in terms of having a negative TCR with a small absolute value and were rated "◎". Cases with a TCR between -60 ppm / ℃ and -50 ppm / ℃ were considered good in terms of having a negative TCR with a small absolute value and were rated "○". On the other hand, cases with a TCR less than -60 ppm / ℃ were considered unsatisfactory due to a negative TCR but a large absolute value and were rated "×". Furthermore, cases with a TCR exceeding 0 ppm / ℃ were also considered unsatisfactory due to a positive TCR and were rated "×". The results are shown in Table 2.

[0131] [5] Overall evaluation

[0132] Among the three evaluation results related to volume resistivity ρ, electromotive force (EMF) of copper, and temperature coefficient of resistance (TCR) mentioned above, the case where all three are rated as "◎" is considered as having excellent volume resistivity ρ, EMF, and TCR, and is rated as "◎". Conversely, the case where one or two of the three evaluation results are rated as "◎" and the rest as "○" is considered as having good characteristics of volume resistivity ρ, EMF, and TCR, and is rated as "○". On the other hand, the case where any one of the three evaluation results related to volume resistivity ρ, EMF, and TCR is rated as "×" is considered as having insufficient characteristics of volume resistivity ρ, EMF, and TCR, and is rated as "×". The results are shown in Table 2.

[0133] [Table 1]

[0134]

[0135] [Table 2]

[0136]

[0137] (Note) Underlined and bold text in the table indicates that the performance evaluation was unsatisfactory.

[0138] As can be seen from the results in Tables 1 and 2, the alloy composition of the copper alloy materials in Examples 1 to 18 of the present invention is within the appropriate range of the present invention, and the three evaluation results related to volume resistivity ρ, thermoelectric potential (EMF) of copper and temperature coefficient of resistance (TCR) are all evaluated as "◎" or "○", and are also evaluated as "◎" or "○" in the comprehensive evaluation.

[0139] Therefore, the copper alloy materials of Examples 1 to 18 of the present invention were all evaluated as "◎" or "○" in the comprehensive evaluation. Thus, they have a high volume resistivity ρ, a small absolute value of copper thermoelectric potential (EMF), and a negative temperature coefficient of resistance with a small absolute value over a wide temperature range from room temperature (e.g., 20°C) to high temperature (e.g., 150°C).

[0140] On the other hand, the alloy compositions of the copper alloy materials in Comparative Examples 1 to 8 are all outside the appropriate range of the present invention. Therefore, for the copper alloy materials in Comparative Examples 1 to 8, at least one of their volume resistivity ρ, thermoelectric potential (EMF) for copper, and temperature coefficient of resistance (TCR) is evaluated as "×".

[0141] Furthermore, in Example 7 of the present invention, with 25.0% by mass of Mn and 10.0% by mass of Ni, and with 0.10% by mass of Co, compared with Comparative Example 1 which did not contain Co and was rated as "×", the absolute value of the copper thermoelectric potential (EMF) was smaller, and therefore it was rated as "○" in the overall evaluation.

[0142] Explanation of reference numerals in the attached figures

[0143] 1. Test materials

[0144] 2 Standard copper wire

[0145] 31, 32 copper wire

[0146] 41. Thermostatic bath

[0147] 42 Freezing point apparatus

[0148] 43 Voltage measuring instrument

[0149] P1 Temperature Measuring Contact

[0150] P 21 P 22 Reference contact

Claims

1. A copper alloy material having the following alloy composition, wherein the alloy composition comprises: Mn: ≥22.0% by mass and ≤35.0% by mass Ni: 5.0% by mass or more, 17.0% by mass or less, and Co: ≥0.10% by mass ≤2.00% by mass The balance is Cu and unavoidable impurities. The volume resistivity of the copper alloy material is 80 × 10⁻⁶. -8 Ω·m and above, When the content of Mn is set as x [mass%], the content of Ni is set as y [mass%], and the content of Co is set as z [mass%], x, y, and z satisfy the relationship shown in equation (I) below. 0.8x-10.5≤y+5z≤0.8x-6.5 (I) When the content of Mn is set as x [mass%] and the content of Ni is set as y [mass%], the ratio of y to x is less than 0.

40.

2. The copper alloy material as described in claim 1, wherein, The alloy composition further contains selected... Sn: ≥0.01% by mass ≤3.00% by mass Zn: ≥0.01% by mass ≤5.00% by mass Cr: ≥0.01% by mass and ≤0.50% by mass Ag: ≥0.01% by mass and ≤0.50% by mass Al: ≥0.01% by mass and ≤1.00% by mass Mg: 0.01% by mass or more, less than 0.50% by mass Si: 0.01% by mass or more, 0.50% by mass or less, and P: At least one of the groups consisting of 0.01% by mass or more and 0.50% by mass or less.

3. The copper alloy material as described in claim 1, wherein, The copper alloy material is in the form of plates, rods, strips or wires, and the average crystal grain size is less than 60 μm.

4. A resistor material for a resistor, comprising the copper alloy material according to any one of claims 1 to 3.

5. A resistor, which is a shunt resistor or a chip resistor having the resistive material for resistors as described in claim 4.

Citation Information

Patent Citations

  • Resistance alloy, member manufactured from resistance alloy, and manufacturing method thereof

    JP2016528376A

  • Resistive material

    JP2017053015A

  • Low melting point cuumn system soldering material having excellent wetting property and fluidity

    JP1981041096A

  • Copper alloy bar, production method for copper alloy bar, resistor resistive material using copper alloy bar, and resistor

    WO2020196791A1

  • Copper alloy strip and method for manufacturing same, resistor resistance material using same, and resistor

    WO2020196792A1